55Mn-ENDOR of the S2-state multiline signal of Photosystem II from Thermosynechococcus elongatus. (19th September 2008) - Pudollek, Susanne; Lendzian, Friedhelm; Bittl, Robert
Abstract : Pulse EPR and 55 Mn-ENDOR (electron nuclear double resonance) experiments at 34 GHz (Q-band) were performed on the S2 state of the OEC (oxygen-evolving complex) in PSII (Photosystem II) from Thermosynechococcus elongatus . The ENDOR spectra are discussed with respect to earlier data obtained from X- (9 GHz) and Q-band experiments on PSII preparations from spinach with and without the addition of methanol.